Pengendalian hama padi secara terpadu di Desa Pulau Rambai Kabupaten Kampar - Hafiz Fauzana; Rusli Rustam; Nelvia Nelvia; Susilawati Susilawati; Husnayetti Husnayetti; Irfandri Irfandri; Wardati Wardati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Rice commodities are the main food and are widely planted in Pulau Rambai Village, Kampa District, Kampar Regency. Pest attacks are the main obstacle in cultivating rice. The concept of integrated pest management (PHT) is applied to rice farmers. This management includes combining compatible pest management techniques, prioritizing natural management using natural enemies. This activity aims to provide counselling, assistance and guidance to rice farmers to implement PHT to increase the quantity and quality of rice production. The intended target was rice farmers in Pulau Rambai Village. The method of implementation carried out is counselling, mentoring and assisting. Counselling is in the form of presentation on farmers' paddy farms introducing the concept of PHT, management of plant cultivation that is not suitable for rice pest development, the introduction of natural enemies of pests, and types of environmentally friendly control such as vegetable pesticides and biological agents. Guidance and mentoring were also given to farmers in monitoring pests, natural enemies, and rice ecosystems. The level of achievement of the program targets was monitored from the questionnaire filled out by farmers before counselling and at the end of the mentoring activities program. From the questionnaire, there was a change in the views and knowledge of farmers in the concept of pest control. The program's achievement is also seen from the change in cultivation methods such as the legowo 4x1 system with three seeds per clump and pest control using biological pesticides according to the guidance.